Effect of Fatigue on the Core Muscle Endurance in Female Athletes With and Without Non-specific Chronic Low Back Pain - Mehri Hajmirzaei Tafreshi; Hooman Minoonejad; Foad Seidi (Physical Treatments, 2023)
Purpose: Non-specific chronic low back pain (LBP) is the most common type of chronic LBP and a common debilitating condition, especially in athletes, that can also affect performance. The core muscles are necessary to create a stable level of support for sports performance and appropriate movements of all organs, and its deficiency is related to complications, such as LBP. This research aims to investigate the effect of a fatigue protocol on core muscle endurance in athletes with and without non-specific chronic LBP. Methods: A controlled laboratory study was conducted; 42 female athletes with and without non-specific chronic LBP were selected through convenience sampling method and divided into two groups with non-specific chronic LBP and without non-specific chronic LBP. McGill’s core endurance test was used to measure core muscle endurance. The measurements were done before and after the implementation of the functional core fatigue protocol (FCFP). SPSS software, version 22 and dependent t-tests and analysis of covariance (ANCOVA) were used to evaluate mean differences obtained in the two groups. The significance level was considered 95%, and the α level was ≤0.05. Results: The analysis of covariance (ANCOVA) showed a significant difference between the two groups with and without non-specific chronic LBP after performing the functional core fatigue protocol (FCFP) in McGill’s test scores in isometric flexion exercise (P=0.001), isometric extensor exercise (P=0.001), right side bridge (P=0.001) and left side bridge (P=0.001). In the post-test measurement, the endurance of the core muscles decreased in the LBP group. Conclusion: The findings revealed that fatigue can affect the core stability and reduce the core muscles endurance of female athletes with non-specific chronic LBP. Therefore, core muscle weakness can be recognized as a risk factor for chronic LBP, and in order to prevent this damage, it is recommended to strengthen this area in rehabilitation programs.